Analisis Tingkat Kesejahteraan Petani Rumput Laut di Kelurahan Songka Kecamatan Wara Selatan Kota Palopo - Rosdiana Idris; M Nur Zakariyah Leo; Ibrahim Abbas (UNM Geographic Journal, 2020)
The objective of this research was to find out the welfare level of seaweed farmers in Songka. This research was a quantitative descriptive research with 35 farmers as samples. The data was collected using a questionnaire based on BKKBN indicators. Furthermore, it was analyzed using descriptive statistical techniques. The results showed that, it can be concluded that working as a seaweed farmer can have a positive impact on seaweed farmers, especially in shifting the welfare level.